Barbara Elling and Andreas Mielke, eds.: Voices from the German Democratic Republic: An Anthology of Contemporary East German Prose - Richard J Rundell (GDR Bulletin, 1987)
Slavic and East European Arts, German Issue, Vol. 3, No. 2 (Fall 1985). Stony Brook, NY: SUNY, 1985. 105 p. $8.00.